"Three essential elements" of the primary health care system: A comparison between California in the US and Guangdong in China. Issue 1 (1st March 2015) - Huang, Minfang; Wei, Donghai; Rubino, Louis; Wang, Lianshen; Li, Dazhuang; Ding, Bofeng; Li, Gan
Abstract : The primary health care system (PHCS) is the portal and basis for the national health delivery system. There are a number of elements which comprise the PHCS, but the system cannot be established and developed without the support of "three essential elements, " including general practitioners (GPs), health insurance, and government health investment. Through comparative analysis of the "three essential elements" of the PHCS between California in the US and Guangdong in China, this article indicates that there are three important aspects in developing a PHCS in China, as follows: training qualified GPs; establishing a diversified health insurance system to strengthen the policy connections between health insurance and the PHCS thereby increasing government health investment; and broadening health financing channels.